Cortical and cerebellar modulation of autonomic responses to loud sounds. (9th September 2013) - Mueller‐Pfeiffer, Christoph; Zeffiro, Thomas; O'Gorman, Ruth; Michels, Lars; Baumann, Peter; Wood, Nellie; Spring, Justin; Rufer, Michael; Pitman, Roger K.; Orr, Scott P.
Abstract Detecting unexpected environmental change causes modulation of autonomic activity essential for survival. Understanding the neural mechanisms associated with responses to loud sounds may provide insights into the pathophysiology of posttraumatic stress disorder (PTSD), since individuals with PTSD exhibit heightened autonomic responses to unexpected loud sounds. We combined fMRI with autonomic psychophysiological assessment to investigate central and peripheral reactivity to loud tones in 20 healthy participants. Activity in anterior insula, pregenual anterior cingulate cortex, anterior midcingulate cortex, supplementary motor area, supramarginal gyrus, and cerebellar lobules VIII–IX was associated with both tones and concomitant skin conductance responses. Since regions signaling unexpected external events modulate autonomic activity, heightened loud tone autonomic responses in PTSD may reflect sensitization of this "salience" network.